INDIVIDUAL CHARACTERITICS IN SECOND LANGUAGE ACQUISITION - Susiati Abas (Al-Lisan: Jurnal Bahasa, 2016)
This paper explores the theoretical framework of the role individual characteristic in language acquisition. In other words, this paper specifies on promoting theoretical justifications of the role individual characteristics in second language acquisition. Language acquisition is very similar to the process children use in acquiring first and second languages. It requires meaningful interaction in the target language-natural communication in which speaker are concerned not with the form on their utterances but with the messages they are conveying and understanding those characteristics are age, gender, intelligence, aptitude, motivation and attitude, personality, learning styles and environment. The development those factors could be conducted via formal and informal language environment. Wherein, informal environment can be quite beneficial for adult second language acquisition. Formal environment are also beneficial. Kajian ini membahas mengenai kerangka teoritis peran karakteristik individu dalam pemerolehan bahasa. Dengan kata lain, kajian ini menekankan pada teori pembenaran mengenai peran karakteristik individu dalam pemerolehan bahasa kedua. Pemerolehan bahasa ini sangat mirip dengan proses pada saat anak menggunakan bahasa pertama dan bahasa kedua. Hal ini memerlukan interaksi yang bermakna dalam bahasa target-alam komunikasi yang fokus pembicaraan tidak lagi pada bentuk-bentuk ujaran but lebih pada makna atau pesan yang disampaikan dan memahami karakteristik tersebut seperti usia, jenis kelamin, intelijen, bakat, motivasi dan sikap, kepribadian, gaya belajar dan lingkungan. Perkembangan faktor-faktor tersebut bisa dilakukan melalui lingkungan bahasa formal dan informal. Dimana, lingkungan informal bisa sangat bermanfaat untuk pemerolehan bahasa kedua oleh orang dewasa. Lingkungan yang formal juga bermanfaat